Pengembangan Modul Berbasis Komputer Untuk Aplikasi Mausu’ah Dalam Penelitian Hadis Oleh Mahasiswa - Syarif Hidayat (SALIHA: Jurnal Pendidikan & Agama Islam, 2018)
The development of a computer-based module for the Mausu’ah application tries to facilitate students to comprehend the Mausu’ah application so that they can do a Hadith research. The objective of this research is to develop a computer-based module for the Mausu’ah application which can be assessed from the instructional, content, appearance and programming aspects by media experts, subject matter experts, students, and those who are competent to assess such a computer-based module for the Mausu’ah application. Besides, the reseacher needs to suggest ways to apply the computer-based module for the Mausu’ah application in an appropriate learning practice, effectively and efficiently. The benefit of using this computer-based module for the Mausu’ah application also needs to be investigated to measure its contribution in the learning process.The development of the module was conducted in several steps, designing, producing, evaluating, revising and socializing the product. Designing process is the first step in the development which was done by identifying and determining the objective, the target, the matter and supporting components. The second process is production in which all collected and compiled materials were arranged to become the initial product. The next process is product evaluation which consisted of some steps; media and subject matter expert evaluation, small group experiment and field experiment. The result of the evaluation is used to revise unproper parts of the product in the revision step. The result of the development showed that all aspects in general were considered good by the students. The instructional aspect had scale average of 3.8, content aspect 3.76, appearance aspect 3.71 and programming aspect 3.74. The average of all aspects were in Good criteria. These criteria indicated that the product of a computer-based module for the Mausu’ah application was worth socializing. The computer-based module for the Mausu’ah application product was applied by using it as additional material for students outside class. Individual learning strategy was viewed as a strategy which was suitable for the product, including this computer-based module for the Mausu’ah application. The result of field experiment showed that the computer-based module for the Mausu’ah application gives positive contribution to student’s understanding, improves student’s motivation in learning and gives stimulus to develop their ability, especially related to the ability to conduct Hadith research.